2017
DOI: 10.1016/j.jcp.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

A Tensor-Train accelerated solver for integral equations in complex geometries

Abstract: We present a framework using the Quantized Tensor Train (QTT) decomposition to accurately and efficiently solve volume and boundary integral equations in three dimensions. We describe how the QTT decomposition can be used as a hierarchical compression and inversion scheme for matrices arising from the discretization of integral equations. For a broad range of problems, computational and storage costs of the inversion scheme are extremely modest O log N and once the inverse is computed, it can be applied in O N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Moreover, tensor networks have the ability to efficiently parameterize, through structured compact representations, very general high-dimensional spaces which arise in modern applications [19,39,50,116,121,136,229]. Tensor networks also naturally account for intrinsic multidimensional and distributed patterns present in data, and thus provide the opportunity to develop very sophisticated models for capturing multiple interactions and couplings in data -these are more physically insightful and interpretable than standard pair-wise interactions.…”
Section: Advantages Of Multiway Analysis Via Tensor Networkmentioning
confidence: 99%
“…Moreover, tensor networks have the ability to efficiently parameterize, through structured compact representations, very general high-dimensional spaces which arise in modern applications [19,39,50,116,121,136,229]. Tensor networks also naturally account for intrinsic multidimensional and distributed patterns present in data, and thus provide the opportunity to develop very sophisticated models for capturing multiple interactions and couplings in data -these are more physically insightful and interpretable than standard pair-wise interactions.…”
Section: Advantages Of Multiway Analysis Via Tensor Networkmentioning
confidence: 99%
“…Because AMEN Cross and related TT rank revealing approaches proceed by enriching low-TT-rank approximations, all computations are performed on matrices of size r k−1 n k ×r k or less. In [CRZ15], it is shown that the complexity for this algorithm is thus bounded by O(r 3 d) or equivalently O(r 3 log N ), where r = max(r k ) is the maximal TT-rank that may be a function of sample size N and accuracy ε. Fig.…”
Section: Algorithm 1 Tt Decompositionmentioning
confidence: 99%
“…Further details about variants of this approach can be found in [OD12,DS13a,DS13b]. The complexity of this algorithm for a maximum TT rank r for both A and A −1 is bound by O(r 4 log N ), as shown in [CRZ15].…”
Section: Algorithm 1 Tt Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, extending the framework of low-rank compression, [9] uses tensor-train compression to re-write K (X, Y ) as a tensor with one dimension per coordinate, i.e., K (x 1 , . .…”
mentioning
confidence: 99%